A Study of Western Expatriates Performance in Algeria: The Role of Cultural Intelligence - Ahmed, BOURAS; Nedjla, KHEZZAR (Sciences humaines; Vol. 42 (2015): SCIENCES HUMAINES (Novembre ), 2016)
consistently suggests that expatriates on assignment require a great deal of support to adjust to their new environment. The cultural environment in which expatriate operate is an important factor for determining successful performance.  The cornerstone of this study is to investigate the influence of dynamic intercultural competency of Cultural Intelligence (CQ) and its dimensions on expatriate job performance.  Analyzing 332 expatriate residing and working in Algeria using Hierarchical regression, we found that Cultural Intelligence (CQ) is a vital intercultural competency that facilitates expatriate job performance in international assignments.  Further, we demonstrated that expatriate in Algeria with greater metacognitive and behavioral CQ fared better in their contextual performance.  Greater assignment specific performance related to greater behavioral CQ.  Keywords : Cultural intelligence, Expatriate, Job Performance, Algeria.          تهدف هده  الدراسة  الى التعرف على طبيعة العلاقة بين الذكاء الثقافي وأبعاده و الأداء  الوظيفي للمغتربين العاملين في الشركات المتعددة الجنسيات    في الجزائر.  الابحاث السابقة على المغتربين تقترح دائما و باستمرار ان المغتربين في مهامهم الوظيفية بحاجة الى قدر كبير من الدعم للتأقلم مع بيئتهم الجديدة.  البيئة التي يعمل فيها المغتربين هي عامل مهم لتحديد الاداء الوظيفي الناجح.هدفت هده الدراسة الى التعريف بمفهوم الذكاء الثقافي و تأثيره على الأداء  الوظيفي على عينة من المغتربين الأجانب والتي بلغ حجمها 332 فردا مقيما ويعمل في الجزائر وهي البيئة المخالفة للبيئة الاصلية للمغتربين.  بنية الدراسة على فرضية رئيسية  مفادها׃هناك علاقة ارتباط إيجابية بين ابعاد الذكاء الثقافي(المعرفة, الدافعية والسلوك) وابعاد الأداء  الوظيفي(أداء المهمة, الأداء السياقية, و أداء المهمة المحددة).وتم تحليل البيانات باستخدام الاساليب الاحصائية: معامل الارتباط البسيط والانحدار الهرمي و توصلت  الدراسة الى مجموعة من الاستنتاجات أهمها:وجود علاقة ذات دلالة احصائية بين الذكاء الثقافي بأبعاده الاربعة و فعالية الاداء الوظيفي بأبعاده الثلاثة. وفي ضوء هذه الاستنتاجات فقد اقترحت الدراسة مجموعة من التوصيات أهمها:ان الذكاء الثقافي هو كفاءة أساسية للتفاعل بين الثقافات او القدرة على التواصل الناجح بين ابناء ثقافة مختلفة والذي يسهل الأداء الوظيفي للمغتربين في المهام الدولية.